Assessment of Bangsamoro Library and Archives’ Online Library Services: Implications to Users’ Information Needs Satisfaction (British Journal of Multidisciplinary and Advanced Studies, 2024)
As technological advancements continue to reshape the landscape of information access, libraries have transitioned to digital platforms to provide a wide array of resources and services. This study aimed to assess the quality of the online library services of Bangsamoro Library and Archives in relation to the satisfaction of the users’ information needs. A modified questionnaire, which was content-validated, and pilot-tested to establish its internal consistency and reliability was distributed to one hundred (100) actual users of the library. Descriptive statistics was used to organize the data on the participants’ assessment of the quality of the online services and users’ information needs satisfaction and regression analysis to determine the significant influence of service quality on the online services on their information needs satisfaction. Findings reveal that participants assessed the quality of online library services considering Affect of Service and Information Control as very good, while participants’ information needs in terms of educational needs and information needs were rated as generally satisfied, indicating that the library has diverse information resources available and can provide online library services needed by the participants for their informational needs. Moreover, the quality of online library services assessment significantly influenced the participants' information needs satisfaction. It is concluded that the public library understudy can cater to the information needs of the community it is serving and services and information resources in the library are being accessed by the users. This study highlights the need for the library personnel to strengthen the area on the Information Control dimension, and the subscription of electronic databases, audiovisual materials, and updated library resources.